Study on HIF-PHI combined with iron supplement in treatment of renal anemia in rats - Zhaoli Gao; Yanxia Gao; Qiang Wang; Qi Wang; Peng Lu; Hailin Lv; Haoran Xue; Xiaotian Ma; Shuen Li; Zhao Hu (BMC Nephrology)
Abstract Background Roxadustat is a novel hypoxia- inducible factor-prolyl hydroxylase inhibitor(HIF-PHI) used to treat anemia in chronic kidney disease (CKD) patients. It has been reported that roxadustat can slow down kidney damage and delay the development of kidney fibrosis. Anemia and iron deficiency are often associated with the vast majority CKD patients, and insufficient available iron or total iron storage is often the most common cause of anemia and ESAs resistance in CKD patients. The role of iron availability in the pathogenesis of anemia in chronic kidney disease has received increasing attention. Objectives To explore whether combined roxadustat and polysaccharide-iron complex (PIC) is more successful than standalone roxadustat, the appropriate iron supplement dosage and mechanism of roxadustat in the treatment of CKD. Materials and methods Healthy male Sprague Dawley rats were randomly divided into two groups: the control (NC) group which were sham-operated and the CKD group. The CKD group was given an adenine diet for three weeks after right unilateral nephrectomy and further divided into 6 groups: the CKD only, CKD + PIC, CKD + Roxa, CKD + PIC (25 mg/kg) + Roxa, CKD + PIC (50 mg/kg) + Roxa, and CKD + PIC (75 mg/kg) + Roxa groups. The sham-operated rats receiving only standard diet served as the control group. Roxadustat were administrated intragastrically at 10 mg/kg thrice per week in groups with Roxa. The hemoglobin (Hb), reticulocyte hemoglobin equivalent (RET-He), reticulocyte % (RET%), plasma urea nitrogen (BUN), plasma creatinine (Cr), serum iron (SI), Total iron binding capacity (TIBC), serum hepcidin-25, interleukin-6 (IL-6), tumor necrosis factor-α (TNF-α), interleukin-1β (IL- 1β), and High mobility group protein B1 (HMGB1) levels of each group of rats were assessed. Masson staining was used to evaluate renal fibrosis, and quantitative real-time Polymerase Chain Reaction (RT-PCR) was used to detect the mRNA expression of alpha-smooth muscle actin (α-SMA) and Fibronectin (Fn) in rat renal tissues to further evaluate renal fibrosis. Results Level of Hb in the CKD + PIC (75 mg/kg) + Roxa group increased the fastest, roxadustat combined with PIC in the treatment of renal anemia was significantly more effective than Roxadustat or PIC alone. On day 105, in the CKD + PIC (75 mg/kg) + Roxa group, there was a significant decrease in BUN and Cr levels compared to the CKD only group (p < 0.05). Roxadustat reduces the level of hepcidin, IL-6, TNF-α, IL-1β and HMGB1in CKD rats. (p < 0.05). Roxadustat alleviates renal fibrosis in CKD rats (p < 0.05). Conclusions HIF-PHI combined with iron supplement (Roxadustat combined with PIC) has an improved effect on the treatment of renal anemia, and early administration of sufficient iron enables the Hb to rise rapidly. Early administration of adequate dose of PIC is necessary for renal anemia. HIF-PHI can improve iron metabolism, alleviate the microinflammatory state, alleviate renal fibrosis and plays a beneficial role in the treatment of renal fibrosis in CKD rats.